Analgesic and anti-diarrhoeal activities of Lagerstroemia speciosa roots in experimental animal model - Hussain, Fahad; Ganguly, Amlan; Hossain, Mohammad Salim; Rahman, SM Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The methanolic crude extract of Lagerstroemia speciosa roots was investigated for its possible analgesic and anti-diarrhoeal activities in experimental animal model. Phytochemical screening of the methanolic extract of L. speciosa roots showed the presence of alkaloids, flavonoids, saponins, tannins and reducing sugar. In acute toxicity study, no mortality or toxic reaction was recorded in animal model after administration of the L. speciosa roots extract. Analgesic activity was evaluated by using acetic acid induced writhing inhibition method in Swiss albino mice. In peripheral method of anti-nociception, the methanolic crude extract of L. speciosa roots showed significant analgesic activity. At the dose of 200 and 400 mg/kg body weight, the extract produced 35.38% and 53.85% (P<0.001) of writhing inhibition, respectively compared to standard diclofenac sodium (70.77% inhibition). The extract had also anti-diarrhoeal activity in castor oil induced method and inhibited the mean number of defecation by 32.75% (P<0.01) and 51.72 % (P<0.001) at the dose of 200 and 400 mg/kg body weight, respectively. The latent period for the extract treated group also increased significantly. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21860 Dhaka Univ. J. Pharm. Sci. 13(1): 57-62, 2014 (June)